Preoperative High-Dose Steroid Has Long-Term Beneficial Effects for Myasthenia Gravis - Syuichi Tetsuka; Ken-ichi Fujimoto; Kunihiko Ikeguchi (Neurology Research International)
Previous studies addressing preoperative steroid treatment have revealed that control of myasthenia gravis (MG) with steroids prior to surgery appeared to stabilize postoperative status. The purpose of our study was to clarify the clinical benefits of the preoperative programmed high-dose steroid treatment on the long-term outcomes of MG patients. We retrospectively reviewed the records of 171 MG patients who were followed up after undergoing thymectomy in our hospital between 1988 and 2006. One hundred and thirteen patients in the programmed treatment group had received preoperative steroid treatment, while 58 patients received no steroid treatment during the preoperative period. Clinical remission, which was defined as the achievement of the modified pharmacologic remission (PR) for at least 1 year, and clinical benefits were compared between the two groups. With regard to the remission after thymectomy, Kaplan-Meier life-table curves for patients in the preoperative steroid treatment group versus those for patients in the no steroid preoperative treatment group revealed a significantly higher probability of the PR in the preoperative steroid treatment group (log-rank test, P<0.01). This study might be the first, as per our knowledge, to indicate that preoperative programmed high-dose steroid treatment has long-term beneficial effects for MG patients.